Penerapan Petunjuk Teknis Operasional ( PTO ) Pada Kegiatan Tridaya LKM Bakti Mandiri Samarinda - -, Fittono - (EKONOMIA, 2014)
LKM Bakti Mandiri is an institution led collegial collective, autonomous, independent, initiated and formed directly by the residents in the village Handil Bakti, with the aim to empower the community, under the auspices of the PNPM Mandiri. Each MFI pelaksananaan Tridayanya Bakti Mandiri activities set forth in the Technical Operational Guidelines, the National Program for Community Empowerment (PNPM), as contained in the circular issued by the Ministry of Interior, represented by the Director General of Community No. 414.2 / 3717 / PMD in 2008.Formulation of the problem in this study is "What Tridaya activities LKM Bakti Mandiri has been run in accordance with the operational standards and technical guidelines that apply? ". The hypothesis in this study is "alleged that the Tridaya activities of LKM Bakti Mandiri has not been in accordance with the operational standards and technical guidelines that apply", where the percentage of responses comparison of measurement results is calculated by dividing the number of answers to the criteria of "good" answer to the whole number.The results showed that the implementation of the tridaya activities of LKM Bakti Mandiri is still not going well, meaning tridaya activities of LKM Bakti Mandiri not in accordance with the operational standards and technical guidelines that apply. This is evident from the calculation of 49 (forty nine) answer "Fine" All the answers were divided by 68 (sixty eight) obtained the percentage of 72.06%.Based on the above calculation and obtained findings showed that the hypothesis is accepted.